2012
DOI: 10.1242/jeb.072082
|View full text |Cite
|
Sign up to set email alerts
|

Flies dynamically anti-track, rather than ballistically escape, aversive odor during flight

Abstract: SUMMARYTracking distant odor sources is crucial to foraging, courtship and reproductive success for many animals including fish, flies and birds. Upon encountering a chemical plume in flight, Drosophila melanogaster integrates the spatial intensity gradient and temporal fluctuations over the two antennae, while simultaneously reducing the amplitude and frequency of rapid steering maneuvers, stabilizing the flight vector. There are infinite escape vectors away from a noxious source, in contrast to a single best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…For example, in a “fly-on-the-ball” paradigm, aversion was not triggered even using a strong repellent [4, 29]. In another study, flying flies responded symmetrically to aversive and attractive odorants [30]. Our more naturalistic approach provided new insights into the relationship between aversive and attractive chemotaxes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a “fly-on-the-ball” paradigm, aversion was not triggered even using a strong repellent [4, 29]. In another study, flying flies responded symmetrically to aversive and attractive odorants [30]. Our more naturalistic approach provided new insights into the relationship between aversive and attractive chemotaxes.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that leaf-cutter ants can discriminate the fungus strain and reject foreign fungus by the odour of the fungus (Ivens et al, 2008). And recently, it has been shown that Drosophila avoid bad smells (Wasserman et al, 2012). The smell might not be directly produced by the parasite, but could be an unavoidable interaction of the parasite and the substrate or stem from the metabolic secretion of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…We chose our repellents mainly on the basis of previous reports on their behavioral activity or -in the case of methyl salicylate -on predictions on the basis of the OSNs they activate and not on the basis of their activity in Flywalk Steck et al, 2012;Wasserman et al, 2012).…”
Section: Response Strategy Towards Repellentsmentioning
confidence: 99%